Application of response surface methodology for modeling and optimization of trichloroacetic acid and turbidity removal using potassium ferrate(VI). Issue 52 (7th November 2016) - Aslani, Hassan; Nabizadeh, Ramin; Nasseri, Simin; Mesdaghinia, Alireza; Alimohammadi, Mahmood; Mahvi, Amir Hossein; Rastkari, Noushin; Nazmara, Shahrokh
Abstract: Coagulation/flocculation and oxidation are two of the main processes in treating colloidal and organic substances. Potassium ferrate(VI), a multipurpose chemical, is used in water treatment plants as coagulant and oxidant. In this study, ferrate(VI) was evaluated for the degradation of trichloroacetic acid and turbidity removal in synthetic water. The effects of five independent variables, initial pH of solution (3–9), ferrate(VI) dosage (1–10 mg L −1 ), contact time (5–60 min), trichloroacetic acid concentration (100–1, 000 μg L −1 ), and initial turbidity (1–10 NTU) were investigated and the process was optimized by means of response surface methodology. Trichloroacetic acid and turbidity removal efficiencies were considered as the process responses. The highest efficiency achieved for trichloroacetic acid removal was 24%, while for turbidity the maximum removal efficiency was in the range 85–95%. The optimum conditions for initial turbidity, pH, and ferrate dosage were 8.89 NTU, 3, and 4.26 mg L −1 as Fe, respectively. Experimentally obtained 89% turbidity removal in the optimum condition confirmed the results predicted by the model. Therefore, it can be concluded that ferrate(VI) can be effectively used in colloidal substances removal, while it is not successful enough in trichloroacetic acid decomposition.